ADD/ADHD/LD [videorecording] understanding the connection - Potts, Marjory; Potts, Robert (Robert A.).; Vineyard Video Productions (West Tisbury, Mass. Vineyard Video Productions, 1997)
Discusses the attention-deficit-disorders and their relationship to learning problems.
Participants: Judith R. Birsh, G. Reid Lyon, Martha Bridge Denckla, Marilyn Jager Adams, Louisa Cook Moats, Joyce Steeves, and others.
Keywords: Learning disabilities; Learning ability; Learning disabled children -- Education; Attention-deficit hyperactivity disorder; Attention-deficit-disordered children; Reading disability; Mathematics -- Remedial teaching